2003
DOI: 10.1177/0310057x0303100308
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the ProSeal and Classic Laryngeal Mask Airways for Airway Management by Inexperienced Personnel after Manikin-only Training

Abstract: We compared the ProSeal™ (PLMA) and Classic™ (LMA) laryngeal mask airway for airway management by inexperienced personnel. Nine nurses from the post-anaesthesia care unit, with no prior experience of LMA or PLMA insertion, were observed inserting the LMA and PLMA in 60 ASA 1 to 2 anaesthetized, paralysed adults following manikin-only training. The time to achieve an effective airway (2 consecutive expired tidal volumes (6 ml/kg; maximum 2 minutes allowed), the number of insertion attempts and the reasons for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 13 publications
(20 reference statements)
1
18
0
1
Order By: Relevance
“…The ProSeal laryngeal mask airway (PLMA; Laryngeal Mask Company) is a variation of the LMA that is more suitable for cardiopulmonary resuscitation, as it has a modified cuff to improve the seal and a drain tube to provide a channel for regurgitated fluid, prevention of gastric insufflation, and insertion of a gastric tube (5). Coulson et al (6) showed that digital insertion of the PLMA and LMA by inexperienced personnel after manikin-only training was equally successful in anesthetized adults, with success rates of approximately 90% after 2 min. Howarth et al (7) described a new insertion technique for the PLMA with a success rate approaching 100% by experienced personnel.…”
mentioning
confidence: 99%
“…The ProSeal laryngeal mask airway (PLMA; Laryngeal Mask Company) is a variation of the LMA that is more suitable for cardiopulmonary resuscitation, as it has a modified cuff to improve the seal and a drain tube to provide a channel for regurgitated fluid, prevention of gastric insufflation, and insertion of a gastric tube (5). Coulson et al (6) showed that digital insertion of the PLMA and LMA by inexperienced personnel after manikin-only training was equally successful in anesthetized adults, with success rates of approximately 90% after 2 min. Howarth et al (7) described a new insertion technique for the PLMA with a success rate approaching 100% by experienced personnel.…”
mentioning
confidence: 99%
“…An 83% success rate has been reported for LMA ProSeal insertion by inexperienced personnel on their first attempt. 2 Several techniques have been introduced to improve the insertion success rate; the use of fibroscopy, 9 an EschmannÒ Tracheal Tube Introducer (i.e., gum-elastic bougie), 4,10 and a suction catheter. 11 However, these techniques do not leave enough oral space for LMA ProSeal insertion; leaving a larger space between the tongue and retropharynx and not requiring the introduction of an index finger would make insertion in children easier.…”
Section: Discussionmentioning
confidence: 99%
“…is an advanced form of the LMA with a softer and larger cuff to improve sealing and a drain tube to permit venting of the stomach. [1][2][3][4] However, when a larger cuff is used, it is more difficult to save space for inserting the LMA ProSeal in the patient's mouth, and the larger cuff is more likely to fold over. 5,6 In particular, LMA ProSeal insertion in pediatric patients may be impeded by a relatively large tongue, a floppy epiglottis, and the frequent presence of tonsillar hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional types of LMAs, such as the LMA-Classic Ò , LMA-ProSeal Ò , or Soft Seal have been reported to be useful for airway rescue [14]. Compared to old types, the Supreme has various enhanced features.…”
Section: Discussionmentioning
confidence: 99%